Profiles of Women With Fibromyalgia and Social Comparison Processes - Terol Cantero, M. Carmen; Buunk, Abraham P.; Cabrera, Victor; Bernabé, Miguel; Martin-Aragón Gelabert, Maite (Frontiers in Psychology, 2020)
Background: Growing interest regarding chronic pain in Fibromyalgia patients, there has been a growing interest in social comparison and its influence on emotional responses. Aims: to analyze profiles in fibromyalgia patients according to pain-perceived, social comparison strategies and anxiety and depression. Methods: The sample consisted of 131 Fibromyalgia outpatients (Mean age: 50.15, SD = 11.1). Two scales were used: the Social Comparison Illness Scale and the Hospital Anxiety and Depression Scale. Results: Two profiles were found by cluster analysis (K-means method): one (66%) with a higher level of pain-perceived, anxiety and depression and greater use of upward contrast and downward identification social comparison; and another (34%) with lower levels of pain-perceived, anxiety and depression and greater use of upward identification and downward contrast. Conclusions: These profiles underline the interest in social comparison strategies and their role in fibromyalgia.